PENGARUH MODEL CIRC DAN TTW BERBASIS LITERASI DIGITAL TERHADAP KETERAMPILAN MENULIS TEKS EKSPLANASI SISWA SEKOLAH DASAR - Suciati Nur Apriyanti, - (2021)
This research is motivated by the low skills of writing explanatory text of students in elementary schools. This study aims to determine the effect of digital literacy-based CIRC and TTW learning models on the explanatory text writing skills of elementary school students. This study uses a quantitative approach with a quasi-experimental method. The research design used the pretest-posttest two treatment design. The samples of this research were students of class VA as the experimental class 1, amounting to 27 students, class VB as the experimental class 2 which amounted to 26. The instruments used in this study were tests and observations. The test was carried out in two stages, namely pre-test before treatment and post-test after treatment. The results showed that the digital literacy-based CIRC model was more influential in improving explanatory text writing skills compared to the digital literacy-based TTW model. This is evidenced by the significance value of the n-gain of the CIRC model is greater than the TTW model, because with this model students learn to work with their group friends to understand the contents of the explanatory text and rewrite the explanatory text according to their experiences.